Long‐range transport of NH3, CO, HCN, and C2H6 from the 2014 Canadian Wildfires. Issue 15 (4th August 2016) - Lutsch, E.; Dammers, E.; Conway, S.; Strong, K.
Abstract: We report the first long‐term measurements of ammonia (NH3 ) in the high Arctic. Enhancements of the total columns of NH3, carbon monoxide (CO), hydrogen cyanide (HCN), and ethane (C2 H6 ) were detected in July and August 2014 at Eureka, Nunavut, and Toronto, Ontario. Enhancements were attributed to fires in the Northwest Territories using the FLEXPART Lagrangian dispersion model and the Moderate Resolution Imaging Spectroradiometer Fire Hot Spot data set. Emission estimates are reported as average emission factors for HCN (0.62 ± 0.34 g kg −1 ), C2 H6 (1.50 ± 0.75 g kg −1 ), and NH3 (1.40 ± 0.72 g kg −1 ). Observations of NH3 at both sites demonstrate long‐range transport of NH3, with an estimated NH3 lifetime of 48 h. We also conclude that boreal fires may be an important source of NH3 in the summertime Arctic. Key Points: First long‐term time series of NH3 concentrations in the high Arctic Boreal wildfire emissions of NH3 detected in Canadian Arctic and Southern Canada 2014 Northwest Territories fires were a considerable source of NH3 in the summertime Arctic